Solution of Amplitude and Solution Domain of the Output Parameter of Disc Cam Mechanism with Floating Roller Push Rod - Fan Wu; Liu Long; Chang Yong (Jixie chuandong)
An important extension about second synthesis task of disc cam mechanism with floating roller push rod is carried out. According to the output parameter travel angle βm of cam- linkage combination mechanism of a high speed printing machine,the existence of a amplitude（βm）maxwhich is the maximum value,and the corresponding "βm solution domain"-( 0,（ βm）max〗are found and revealed. The preceding study found that,regardless of digging the potential of existing mechanisms or scalable coverage,all has important theoretical value and practical engineering significance.